Startup and Innovation Technology: Innovation ecosystems to improve agro-commercial business performance in La Troncal - Verdugo Ortega, Adriana Nicole; Jara Obregón, Luis Stalin (Journal of business and entrepreneurial studie, 2023)
The following research arises as part of a project that aims to conduct a study for the implementation of emerging IT tools or startup for the business and agricultural area of the canton La Troncal, for which we have taken a mixed research methodology that will allow us through analysis of reports and studies conducted by government organizations, NGOs and interviews with business owners who provide precision agriculture services such as spraying with drones in the study area. Having as main objective a review of the current situation of the problem to identify the main innovation ecosystems needed to improve the performance of agro-commercial businesses in the Canton La Troncal.